Understanding the in vitro gastrointestinal transit tolerance of putative lactic acid bacteria isolated from Malaysian fermented foods. - Low, Siew Jean (2021)
Probiotics are defined as living microorganisms that when consumed in adequate amounts will exhibit health benefits to the host. Probiotics are known to play important roles in relief of lactose intolerance symptoms and improving gut health. However, till today the beneficial effect of probiotic bacterium is strain-specific, no single probiotic is able to resolve all gut health issues. Hence, the search for a stronger and more potent of probiotic bacterium is essential. Hence, the current study is aimed to isolate putative lactic acid bacteria from local fermented foods, namely tempeh and tapai ubi, and investigate the ability of these LABs to tolerate the upper gastrointestinal transit in an in vitro setting prior to future use as probiotics. A total of 18 putative LABs were isolated from tempeh and tapai ubi using spread plate method with MRS selective medium. However only four isolates remained viable after frozen storage and was proceeded for subsequent studies.